Developing a digital-based practical Qur'an learning book for prospective early childhood teachers - Saptiani Saptiani; Rahmi Sofyan (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
This study aims to develop a digital-based practical Qur'an learning book for prospective early childhood teachers. This research and development use Alessi and Trollip model with three steps; planning, design and development. Media experts and product material experts validated the product's feasibility. Then, the product was tested on prospective early childhood teachers in Langsa. The results of the development of practice materials for learning the Qur'an based on digital books through media experts before the revision was 68% and increased after being revised to 84%, while the score from material experts before the revision was 56% and increased after the revision to 76%. The teacher was tested first to measure competence in reading the Qur'an using an unfeasible product, and then the second stage test was carried out. Therefore, the revised product shows that the practical Qur'an learning book is feasible to use as a learning medium to improve the competence of prospective early childhood teachers in reading and teaching Qur'an.